A study of the gas interference effects in quadrupole mass spectrometer. (1st June 2022) - Yongjun, Cheng; Meng, Dong; Wenjun, Sun; Suzhao, Zhang; Xinghui, Wang; Xiangmin, Wu; Lan, Zhao; Lian, Chen; Chengyao, Wu; Yi, Song; Ruifang, Zhang
Abstract: In most applications, it is significant to understand how the composition and total pressure of the gas affect the sensitivity of a mass spectrometer for a specific composition of the gas. This work reports on the interference effects of the QMG700 quadrupole mass spectrometer (QMS) with the use of the ultrahigh vacuum partial pressure standard apparatus and standard leaks. Six combinations for Ar–H2, Ar–He, N2 –H2, He–H2, He–N2 and CH4 –N2 –Ar–He–H2 gas mixtures were selected for the study of the instrument–gas interaction. The partial pressures of the interference gases varied in the range of 2.2 × 10 −7 –8.3 × 10 −3 Pa, and the total pressures of the calibration chamber ranged from 1.2 × 10 −5 Pa to 9.9 × 10 −3 Pa. The detector of the QMS utilized only a Faraday cup, and the results demonstrated that the sensitivity of the trace gas was significantly affected by the interfering gas when the total pressure exceeded about 10 −5 Pa. This study was also performed according to ISO TS 20175:2018.